PERANCANGAN DAN PEMBUATAN SISTEM INFORMASI PELAYANAN KONSULTASI HUKUM BERBASIS WEB PADA KANTOR HUKUM MR. OKY & PARTNERS - Melani Ariska Putri; Asri Dewi; Ade Rayhan; Sharyanto Sharyanto; Alexius Ulan Bani (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
MR. OKY & Partners Law Office faces challenges in managing legal consultation services, as processes such as client data recording, document management, and consultation scheduling are still handled manually. This results in less effective and efficient services and potential data security risks. This study aims to design and develop a web-based legal consultation information system to improve service quality. The research methods include observation, interviews, and literature study, with system design using Unified Modeling Language (UML). The system is implemented using PHP and MySQL and tested using Black Box Testing. The results show that the system improves data management efficiency, accelerates document retrieval, and enhances service effectiveness.